2021
DOI: 10.1002/adfm.202010254
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Protective Film: Ultrahard, Yet Flexible Hybrid Nanocomposite Reinforced by 3D Inorganic Nanoshell Structures

Abstract: Emerging flexible optoelectronics requires a new type of protective material that is not only hard but also flexible. Organic–inorganic (O–I) hybrid materials have been used as a flexible cover window to increase wear resistance and polymer‐like flexibility. However, the hardness of O–I hybrid materials is much lower than that of metals and ceramics due to the low intrinsic hardness of the organic matrix and limited volume fraction of inorganic reinforcement. Herein, a new type of hybrid nanocomposite combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Through the development of micro-/nanotechnologies, it has been proven that nano-physicochemical properties (including the stretchability and thermoelectric and photocatalytic properties) originating from various classes of 3D nanostructures can be successfully extended to bulk properties through an inch-scale production of the pattern [40,53,65,[83][84][85][86][87]. A wide range of high-value-added applications such as energy storage systems [60,[88][89][90][91][92][93][94], optical films [95], structural materials [96][97][98][99][100], and sensory devices [39,58,[101][102][103] have since become possible to implement through a wafer-scale production. It should be mentioned that the material substitution from a 3D polymeric template into ceramic, metal, and organic functional materials through atomic layer deposition [84-87, 89, 91, 95, 98], electroplating [60,83,88,93], and infiltration [40,53], respectively, can be used to expand the technical functionality during this 3D nanofabrication process.…”
Section: Realization Of Large-area 3d Nanopatternsmentioning
confidence: 99%
“…Through the development of micro-/nanotechnologies, it has been proven that nano-physicochemical properties (including the stretchability and thermoelectric and photocatalytic properties) originating from various classes of 3D nanostructures can be successfully extended to bulk properties through an inch-scale production of the pattern [40,53,65,[83][84][85][86][87]. A wide range of high-value-added applications such as energy storage systems [60,[88][89][90][91][92][93][94], optical films [95], structural materials [96][97][98][99][100], and sensory devices [39,58,[101][102][103] have since become possible to implement through a wafer-scale production. It should be mentioned that the material substitution from a 3D polymeric template into ceramic, metal, and organic functional materials through atomic layer deposition [84-87, 89, 91, 95, 98], electroplating [60,83,88,93], and infiltration [40,53], respectively, can be used to expand the technical functionality during this 3D nanofabrication process.…”
Section: Realization Of Large-area 3d Nanopatternsmentioning
confidence: 99%
“…Recently, Bae et al reported the ultrahard yet flexible 3D hybrid nanocomposite film combining an epoxy-siloxane molecular hybrid (ESMH) as a polymeric matrix and BCT Al 2 O 3 as the reinforcement phase. 70 The BCT Al 2 O 3 evenly distributed in the ESMH matrix significantly enhances the hardness and impact resistance of the nanocomposite, while simultaneously maintaining high flexibility and optical transparency. The 3D hybrid nanocomposite achieves metal-like hardness (1.3 GPa with 17.1 vol % of Al 2 O 3 ), significantly higher than those of the conventional polymerbased nanocomposites.…”
Section: Nanoarchitected Materials Fabricated By Pnpmentioning
confidence: 99%
“…Our research team has previously reported organic–inorganic hybrid materials made by siloxane networks, which showed excellent stability against humid, thermal, mechanical, and chemical stresses. , The hybrid materials were made into a transparent and flexible film structure through simple curing and compressing processes. Although the hybrid material-based films have been used as dielectric layers, LED encapsulants, and nanoparticle (NP)-dispersed films, , their stabilities as f-μLED substrates and passivation layers have not been exploited in various harsh environments yet.…”
Section: Introductionmentioning
confidence: 99%